Fenomena Pengamen Al-Qur’an dan Implikasi Sosial Keagamaannya - HS, Fatimah; HS, Muhammad Alwi; Muflihah, Muflihah (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
This article discusses the phenomenon of Al-Qur'an Singers (PQ) which is widely found in Makassar, South Sulawesi, especially as a functional reception of Al-Qur'an as well as a review of Islamic law on it. This article argues that reading Al-Qur'an is a performing phenomenon in order to influence others. As a consequence of the performance, reading Al-Qur'an is good or bad based on its motives and impact. In discussing PQ, this article uses a type of field research, with primary sources in the form of interviews, observation, and documentation, while secondary sources are obtained from various relevant literature on the topic of study. These data are presented using a descriptive-analytical method based on a qualitative approach. This article concludes that the PQ phenomenon cannot be separated from the socio-religious construction of Makassar Muslims towards Al-Qur'an, as their Holy Book. PQ appears and develops in spaces and contexts relevant to Al-Qur'an’s functioning to get rewards from street users. In this socio-religious construction, PQ becomes a job that cannot be judged in black and white, namely halal or haram, because PQ shows uncertain (fixed) motives and impacts.